BO‘LAJAK O‘QITUVCHILARNI TURIZM FAOLIYATIGA TAYYORLASHNING PEDAGOGIK-PSIXOLOGIK XUSUSIYATLARI (Scientific journal of the Fergana State University, 2024)
This article describes the concept of tourism, the essence of cultural tourism and museum tourism, tourism development factors, tourism and museum cooperation, the importance of museums in the development of cultural tourism. The educational tasks of tourism activities, the nature of educational tourism, educational excursions, and foreign experiences on the preparation of future teachers for tourism activities at pedagogical universities, and the three-block pedagogical features of preparing future teachers for tourism activities through museum pedagogy explained. The role of pilgrimage and tourism in the spiritual-psychological and aesthetic education of the future teacher is emphasized. Also, the characteristics of the aesthetic education of tourism in the activities of the future teachers are defined in a certain sense and its main tasks. For future teachers, tourism activity is based on the unique educational function of spreading cultural values, changing their thinking and worldview, educating a well-rounded person.